Flexible Wood Composites from Rigidity to Twistability via Advanced Fabrication for Multidisciplinary Applications - Pork, Fredrik; Lunder, Michael; Liverty, Jecob (Journal of Green Energy and Environmental Engineering, 2023)
Petroleum-based flexible composites face critical bottlenecks of non-degradability, high carbon footprint, and resource depletion, despite their excellent bendability. Wood, with its hierarchical porous architecture and renewable nature, offers an ideal substitute for petroleum-based matrices; however, cross-scale flexibilization mechanisms remain poorly systematized. This review systematically examines recent advances in the emerging field of flexible wood composites (FWCs). We begin with cross-scale structures from cellulose molecules to thin veneers, categorizing two primary flexibilization strategies: (i) the wood fiber route, encompassing melt compounding, continuous flat-pressing, and additive manufacturing; and (ii) the thin veneer route, involving lignin removal and polymer lamination. Their processing-structure-property relationships are critically evaluated. We further highlight state-of-the-art applications of FWCs in green construction, smart sensing, energy storage, environmental remediation, and biomedicine. Challenges for scalable implementation—environmental consistency, long-term durability, and functional integration—are also analyzed. Finally, future pathways are outlined for frontier applications including tissue scaffolds, shape-memory devices, and embodied intelligent systems. This review provides technical guidelines for cross-scale wood flexibilization across diverse scenarios, advances FWCs as a green alternative to petroleum-based functional materials, and supports high-value wood utilization toward carbon neutrality and sustainable material innovation.